VAN DER RIET, JW Inventory of documents - VAN DER RIET, JW (ARCA, 2018)
General practitioner; Member of the Council of the University of the Orange Free State (1964)
COVERAGE 1921-1973; 1.00 metre
Keywords: VAN DER RIET, JW; College of Medical Practitioners; UFS Medical Library; Orange River Water scheme; Pelonomi Hospital; UFS Medical Faculty; Medical Training South Africa